Modelling the environmental and socio-economic impacts of controlling the invasive prosopis tree in Witbank, Northern Cape, South Africa - Sishuba, Lungisa (Stellenbosch : Stellenbosch University, 2023)
Thesis (MPhil)--Stellenbosch University, 2023.